Trump Digs Votes - The Effect of Trump's Coal Campaign on the Presidential Ballot in 2016 - Marina Di Giacomo; Wolfgang Nagl; Philipp Steinbrunner (Center for Economic Studies and ifo Institute (CESifo), 2022)
In this paper we investigate the effect of Donald Trump's campaign for coal in his successful race for the White House in 2016. Using a spatial Durbin model we estimate the effect of coal production on the Republicans vote share in the US Presidential Election of 2016 on the county level. To avoid biased estimates we take spillover effects into account and use spatial clustering. We find a significant positive effect. The effect becomes even more pronounced when we use the vote-share difference between Mitt Romney in 2012 and Donald Trump in 2016 as the dependent variable. The positive effect of coal production on the Republican vote share are retained after allowing for non-linear effects of coal production and using coal production per worker and per working hours as main explanatory variable.
Keywords: D72; P16; P18; R11; 330; US Presidential Election 2016; coal production; Durbin model